Hootsuite: In Pursuit of Reactive Systems. - Steel, Edward; Berube, Yanik; Bonér, Jonas; Britton, Ken; Coatta, Terry (Communications of the ACM, 2017)
An interview on the topic of software as a service (SaaS) social media platform firm Hootsuite is presented with several Hootsuite officials and employees including Hootsuite senior Scala developer Edward Steel, Lightbend chief technology officer (CTO) Jonas Bonér, and Marine Learning Systems CTO Terry Coatta.